TERRITORIAL COMMUNITY UNDER STATE POLICY DEVELOPMENT OF URBANIZED TERRITORIES OF HISTORICAL CITIES - Kravchenko S.G. (Pressing Problems of Public Administration, 2016)
Analysis of urbanized territories of historical cities has been made and their impact on community development in the areas where monuments of national signi cance are located evaluated. Speci c features, status of monuments and the level of communities’ responsibility for their preservation and adaptation to future use have been considered. Concrete examples of resolving the said issues at the local level are given. The main directions of further development of communities, which are located in the zone adjacent to historical areas, have been determined.